Kelezatan yang Menggoda: Temukan Keistimewaan Selai Kacang Mete dari Desa Medana, Lombok Utara - Baiq Merozza Kinasih Sandya (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
This study focuses on the implementation and outcomes of Community Service Activities (PKM) in Medana village. The purpose of the PKM is to enhance the value of local cashew nuts and create better economic opportunities for the residents. The PKM program is designed as an innovation initiative, employing a simulation and practice approach. The main result of the PKM activities is the increased knowledge and ability of the community members to independently produce high-quality cashew nuts, leading to an increase in their market value. The contribution of this study lies in providing the residents of Medina village with new skills in processing cashew nuts into delicious and savory products. This research highlights the significance of savory innovation, particularly in the production of cashew jam, and its potential impact on the socioeconomic development of Medana village in North Lombok.